Upaya Memantapkan Pilihan Sekolah Lanjut melalui Layanan Penguasaan Konten di MTs Negeri 7 Gunungkidul - Nuryani Ikaria (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
This research aims to analyze the role of content mastery services in helping students determine their secondary school. An approach to counseling guidance services in this case is necessary to assist students in determining and planning for the future. This research uses a method of action. The subject of the study was grade IX-B students at MTs Negeri 7 Gunungkidul. The results showed an increase in students in establishing advanced school choice in cycle I by 77.6% increasing to 89.4% chest cycle II. The results of the content mastery service approach in two cycles successfully assisted students in establishing advanced school choice in MTs Negeri 7 Gunungkidul.